2008
DOI: 10.1509/jmkr.45.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Art Infusion: The Influence of Visual Art on the Perception and Evaluation of Consumer Products

Abstract: for their help in creating some of the stimuli used in this article. Chris Janiszewski served as associate editor for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
319
1
25

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 422 publications
(364 citation statements)
references
References 26 publications
19
319
1
25
Order By: Relevance
“…To keep the products in the public eye, the retailer have to demonstrate products artistically encourage customers to connect with the merchandise at their sensual level. The art of shifting customer preferences of everyday products was investigated by Hagtvedt and Patrick (2006) and this art infusion theory not only influences evaluations, but also has a capacity to reduce emotional responses (Darso, 2013). It has been observed that during festive season retailer sales their products with decorative packaging or in decorated shopping bags, reused by the customer as gift bags or as shopping bags.…”
Section: Arts As Decorationmentioning
confidence: 99%
“…To keep the products in the public eye, the retailer have to demonstrate products artistically encourage customers to connect with the merchandise at their sensual level. The art of shifting customer preferences of everyday products was investigated by Hagtvedt and Patrick (2006) and this art infusion theory not only influences evaluations, but also has a capacity to reduce emotional responses (Darso, 2013). It has been observed that during festive season retailer sales their products with decorative packaging or in decorated shopping bags, reused by the customer as gift bags or as shopping bags.…”
Section: Arts As Decorationmentioning
confidence: 99%
“…In the case of artists, consumers may more readily activate favorable associations similar to those linked to luxury brand designers (particularly regarding skill and status). Essentially, the words "luxury" and "arts" are conceptually interlinked (Hagtvedt and Patrick 2008); branding scholars (Kapferer and Bastien 2009a, p. 74) even recommend that managers of luxury brands "cultivate closeness to the arts for [luxury] initiatives." Indeed, luxury brands often market collections designed by artists (e.g., tattoo artist Scott Campbell or modern artist Takashi Murakami for Louis Vuitton; artist Irena Komadinic codesigning a collection of couture dresses for the luxury fashion brand Breeyn McCarney).…”
Section: How Labeling Products As User Designed Backfires / 79mentioning
confidence: 99%
“…A different perspective on the effect of plating on participants' responses to the food would be to consider the ' Art-Infusion' phenomenon as advanced by Hagtvedt and Patrick [37]. According to this theory, consumers evaluate products more favourably when they are associated with art.…”
Section: Art-infused Food Designmentioning
confidence: 99%